Salsa: Leveraging Email to Create a Social Network for the Enterprise - Counts, Scott (2009)
In this paper we describe Salsa, a plug-in that aggregates social and other content into an email client. Information in Salsa is collected from a variety of sources both inside and outside of email to create a profile for each person in our corporation that contains a photo, organizational details, friends, and an aggregated feed of shared content. Thus, Salsa uses a social networking approach to add social awareness to email. Salsa was deployed internally within our corporation and we trace its growth for six months and describe the results of a targeted user study. Findings demonstrate the extent to which and what type of social awareness is useful in our organization. Use of the aggregated feed is also discussed. In addition to identifying features that are useful for social networks in the enterprise, we explore the benefits of situating this type of application in email.